Research on proportional method for experimental facility of lead-based fast reactor with natural circulation. (July 2022) - Zhao, Pengcheng; Wang, Ting; Zhu, Enping; Wang, Tianshi; Wang, Yuxuan
Highlights: The main similarity groups determined by using dimensionless equations in typical lead-based fast reactors with natural circulation. The proportional method of natural circulation LFR was carried out to obtain the geometric and thermal–hydraulic design parameters of the experimental facility. The research results show that the proportional method established here is reasonable and feasible. Abstract: Lead-based fast reactors exhibit outstanding natural circulation capabilities, and their natural circulation characteristics are highly valuable for improving the inherent safety of reactor. The existing proportional method forms the theoretical basis for establishing a reasonable and feasible experimental facility that can help study the lead-based fast reactor with natural circulation. In this study, the main similarity groups could be determined by using dimensionless equations of primary cooling systems in typical lead-based fast reactors with natural circulation. Based on the constructed dimensionless similarity groups, the proportional method of a small lead-based fast reactor (Small Natural circulation Lead-based Fast Reactor (SNCLFR-10)) with natural circulation was carried out to obtain the geometric and thermal–hydraulic design parameters of the experimental facility. The proportional method was verified by comparing and analyzing the key thermal and hydraulic parameters of SNCLFR-10 and the experimental facility under rated conditions. The research results show that the key thermal–hydraulic parameter ratios of SNCLFR-10 and the experimental facility are in good agreement with the theoretically deduced ratios, thereby ensuring that the proportional method established here is reasonable and feasible.